Treatment of Bovine Papilloma: Mohammed A. Hamad 1 , Anton S. Al-Banna2 and Nahi Y. Yaseen3 - Hamad, Mohammed A. (The Iraqi Journal of Veterinary Medicine, 2012)
In this study (35) cows suffering from bovine papilloma were subjected for three differenttypes of treatments; The First group involved 15 animals treated with autogenous vaccine.The Second group involved 10 animals treated with prepared cell culture vaccine .While thethird group involved 10 cows treated with virulent local Newcastle disease virus. In the Firsttwo groups the warts were surgically removed from cows showing lump lesions on skin ofabdomen, neck and udder, and transferred aseptically to laboratory by using transport media.Treatment of cows in the first group involved preparation of autogenous formalin (0.5%)in activated vaccine. Vaccination of these animals result in regression of the warts startedafter 2 or 3 weeks and complete disappearance of the warts after 30-60 days with a meanduration of 44.9 days.Treatment of the second group involved preparation of papilloma cell culture inactivatedvaccine 0.5% formalin from 3 papilloma cases. The response of these vaccinated cows resultin regression of the warts lesions started after 2 or 3 weeks post the first vaccinal dose andcomplete disappearance of the warts after 30-60 days, with mean 43.8 days.Treatment of the third group involved using of virulent NDV by subcutaneous injectionand infiltration around the warts. Results showed successful regression of warts within ashorter period with mean of 30.1 days compared to treatment with autogenous and cell culturevaccine, with complete regression of the warts within 15-28 days.